Protection of the Rights of Sharia Insurance Customers According to Islamic Economic Law - Tolhah Toha Nawawi (Fox Justi : Jurnal Ilmu Hukum, 2025)
This study aims to analyze the protection of Sharia insurance customers' rights from an Islamic economic law perspective. Sharia insurance offers an alternative risk protection system based on the principles of mutual assistance (ta'awun), mutual protection (takaful), justice, trustworthiness, and freedom from riba, gharar, and maisir. However, in practice, various problems remain related to the implementation of Sharia principles, particularly in terms of transparency, fulfillment of customer rights, and dispute resolution mechanisms. The research method used is normative legal research with a juridical and conceptual approach. Data were obtained through a literature review of primary, secondary, and tertiary legal sources, including the Quran, Hadith, fatwas from the National Sharia Council (DSN-MUI), laws and regulations, and relevant scientific literature. The data were analyzed descriptively and qualitatively to understand the alignment between Sharia insurance practices and Islamic legal provisions. The results indicate that the protection of customer rights in Sharia insurance has a strong legal basis, both normatively and juridically. This protection includes the right to clear information, trustworthy fund management, fair treatment, fulfillment of benefits according to the contract, and access to equitable dispute resolution. However, optimizing protection still requires increased oversight, transparency, and customer education. With the consistent application of Islamic economic law principles, it is hoped that the Islamic insurance system will be able to provide fair, transparent, and sustainable legal protection for customers.